TARIAN LAKA BAKA KEPULAUAN SULA - Syahril Muhammad; Rustam Hasim (Jurnal GeoCivic, 2024)
The Laka Baka dance is seen as part of dance activities like those in other areas, while the spirit of values that exist implicitly is no longer the focus. The younger generation only views dance as an ordinary performance. There is even concern that if the values contained in it are not looked into in depth, it is certain that Laka Baka will lose its identity in the future. The Laka Baka dance is a cultural identity of the people of the Sula Islands whose existence has been around for a long time and has grown over hundreds of years. The Laka Baka dance teaches people about the value of patriotism and the spirit of community life with high motivation. The Laka Baka dance is a form of honorary dance which is always used in cultural events in the Sula Island community, because this dance is always used as a welcoming dance for guests of honor.